Pengaruh Celebrity Endorsement, Harga, dan Kualitas Produk terhadap Keputusan Pembelian Skincare BG Skin Cabang Sampang - Wulan Mauludina Ahmad; Nur Farida; Nur Aini Anisa (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to determine the influence of celebrity endorsement, price, and product quality on purchasing decisions of BG Skin skincare products among users at the BG Skin Branch Sampang. The research method used is quantitative with a survey approach. Data were collected by distributing questionnaires to 43 respondents who have used BG Skin products. The data analysis techniques employed include validity and reliability tests, classical assumption tests (normality, multicollinearity, and heteroscedasticity), multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The results of the study indicate that the variables of celebrity endorsement, price, and product quality simultaneously have a significant effect on purchasing decisions. However, partially, only price and product quality have a significant influence on purchasing decisions, while celebrity endorsement does not have a significant effect. The coefficient of determination (R²) value of 0.415 indicates that 41.5% of the variation in purchasing decisions can be explained by the three independent variables.